Three new species of Pelidnota MacLeay (Coleoptera, Scarabaeidae, Rutelinae) and new distributional records from northeast Brazil - Ferreira,André da Silva (2017)
Abstract Three new species of Pelidnota MacLeay, 1819 are described from Brazil, P. beckeri sp. nov., P. nordestina sp. nov., and P. pernambucana sp. nov. The diagnostic characters of the new species are presented, and they are included in the previously published key to Pelidnota. Illustrations of the male genitalia and photographs of males and females of the new species are also provided. It is reported the first record of the genus for the Brazilian Caatinga (tropical seasonal forest). New records of four species and two subspecies of Pelidnota are presented, all from Bahia state, northeastern Brazil.